Insights Into Medical Communication - Sala, Michele; Sala, Michele; Gotti, Maurizio; Maci, Stefania Maria (Peter Lang, 2015)
This book analyses the subject of medical communication from a range of innovative perspectives, covering a broad spectrum of approaches and procedures that are particularly significant in this field. In this volume, medical communication is analyzed from various viewpoints: not only from a merely linguistic angle, with a focus on the description of the genres used in medical and healthcare contexts, but also from a social and cultural standpoint, with an emphasis both on the doctor-patient relationship and on the social relevance of the other types of communicative links existing between the many communities involved in this type of interaction. The study of some of the main fields typical of medical communication has highlighted a considerable variety of themes, data and research methods which are clearly representative of the eclectic interest in this specific domain and of the wide range of approaches developed for its investigation. As the various chapters show, linguistic analysis proves to be highly applicable to textualizations involving multiple interactions and practices, and several kinds of participants, including different healthcare professionals, trainees and patients.